HUBUNGAN TINGKAT KONSUMSI Fe, VITAMIN C DAN STATUS ANEMIA DENGAN KEJADIAN DISMENOREA PADA REMAJA PUTRI DI SMA NEGERI 1 SUKAWATI - Ni Wayan Anisa Casteli (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2018)
Dysmenorrhea is a physical disorder of abdominal pain before and during the menstrual period, that occurs without the infection signs or pelvic disease. One of the causes of dysmenorrhea is anemia. Anemia occurs because someone has deficiency of iron and intake of vitamin C. The purpose of this research is to knowing the relation between consumption level of Fe, vitamin C and status of anemia with dysmenorrhea incidence of teenage girls in SMA Negeri 1 Sukawati. The type of this research is observasional research with the cross sectional design. This research was conducted on 79 teenage girls in SMA Negeri 1 Sukawati. The variables of this study were collected by 24 hour recall method, measurement of Hb level and by using questionnaires. The result of this research showed there were 78 samples (99%) that had less consumption level of Fe and 65 samples (82%) had less consumption level of vitamin C. 32% samples of this research were anemia and 76% samples were dysmenorrhea. According to the chi square analysis result there wasnt relation between consumption level of Fe (p = 0,356) and vitamin C with status of anemia (p = 0,479). And there wasnt relation between status of anemia with the incidence of dysmenorrhea (p = 0,567). Keywords : Dysmenorrhea, anemia, Fe consumption, vitamin C consumption